Colour properties and colourfastness of silk fabrics dyed with lichen dyes extracted using microwave, ultrasound and enzyme-assisted extraction methods / Nor Atiqah Mohamed - Mohamed, Nor Atiqah (2016)
Although the presence of widely available and cheaper synthetic dyes almost substituted the use of natural dyes, the use of natural dyes for dyeing textile materials has now become a greater interest because they are more ecofriendly than synthetic dye. There is awareness amongst consumers and the textile industry for the need to reinvert natural dyes to impart colour to textiles. Lichens have been the source for natural dyes to colour textiles in many parts of the world. In Malaysia, studies on lichens have so far focused on their distribution, chemistry and biological activities and there is no exact reference on textile dyes. Extraction of colour component from source natural dye material is important step for dyeing any textile substrates to maximize the colour yield. In this study, to explore the colouring potential of local lichen species, silk fabric, which is a very good base for natural dyes, was dyed with lichen dyes produced using different extraction methods. In the first phase, several species of lichens were extracted using boiling water, boiling seawater, solvent and ammonia fermentation methods. The colours were further altered using six different mordants with meta-mordanting technique. In the second phase, two lichens species were selected (P. praesorediosum and H. leucomelos) for colour extraction using microwave (MAE), ultrasound (UAE), microwave-enzyme-assisted (MEAE) and ultrasound-enzyme-assisted (UEAE). The predominant dye colours were soft shade of brownish and yellowish tones but pink were also produced by the addition of vinegar to the ammonia extract. The effect of the different extraction methods were investigated for colour properties and colour fastness on the silk dyed fabrics. It was found that the colour values were influenced by the addition of mordants. The results also indicate that percent yield, dye uptake and colour strength with the MAE, UAE and enzyme-assisted extraction methods increased compared to BWM method. The dyed silk samples which were tested for colour fastness to washing, perspiration, rubbing and light, gave good to excellent ratings. It is expected that the methods used in the research could be employed for extracting colouring from other natural materials in a faster and effective manner. Lichen dyes and colours are visually pleasing and have potential to be introduced in the textile dyeing or printing industries particularly batik manufacturers and natural product lovers.